Traditional Handicrafts and Cultural Identity: The Case of Orang Ulu in Miri, Sarawak - Alexander, Chelum; Muhammad Azri, Ali; Laura Pranti, Tutom; Muhammad Qawiem, Hamizan (Human Resource Management Academic Research Society (HRMARS), 2025)
This study investigates the role of traditional handicraft economic activities in sustaining the cultural identity of the Orang Ulu community in Miri, Sarawak. While extensive research has examined Sarawak’s Iban and Malay crafts, Orang Ulu handicrafts remain underexplored, particularly within urban contexts where traditional practices are recontextualized for new markets. Addressing this gap, the study adopts a qualitative design framed by Cultural Capital Theory (Bourdieu, 1986) and Cultural Economics (Throsby, 2001) under an interpretivist paradigm. Data were collected through semi-structured interviews, non-participant observations, and field visits with ten purposively selected artisans and traders. Findings reveal that handicrafts such as Sabu bead necklaces, Tebilang sashes, Ta’ah attire, and the Sape’ lute operate as visual languages of clan histories and spiritual values, while simultaneously serving as economic goods within markets, exhibitions, and cultural tourism. However, artisans face structural challenges including scarcity of raw materials, rising costs, market imitations, and limited digital marketing skills. The study contributes to cultural economics and heritage studies by situating Orang Ulu handicrafts as both cultural capital and creative economy resources. It concludes that sustaining these traditions requires systemic interventions in ecological conservation, intellectual property rights, digital literacy, and cultural education. By highlighting the intersection of heritage and economy in an urban Malaysian context, this research extends debates on indigenous resilience and the negotiation of authenticity in global craft markets.